2023
DOI: 10.3390/ijms24044158
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insight into Intraspecies Distinctions in Pseudoalteromonas distincta: Carotenoid-like Synthesis Traits and Genomic Heterogeneity

Abstract: Advances in the computational annotation of genomes and the predictive potential of current metabolic models, based on more than thousands of experimental phenotypes, allow them to be applied to identify the diversity of metabolic pathways at the level of ecophysiology differentiation within taxa and to predict phenotypes, secondary metabolites, host-associated interactions, survivability, and biochemical productivity under proposed environmental conditions. The significantly distinctive phenotypes of members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…While preparing this article, a study was published wherein the P. elyakovii VKPM B‐3905 T genome was presented (Balabanova et al, 2023). Unexpectedly, the newly sequenced isotype did not cluster with the other two P. elyakovii type strain genomes and was sister to P. shioyasakiensis JCM 18891 T in the phylogenomic tree (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…While preparing this article, a study was published wherein the P. elyakovii VKPM B‐3905 T genome was presented (Balabanova et al, 2023). Unexpectedly, the newly sequenced isotype did not cluster with the other two P. elyakovii type strain genomes and was sister to P. shioyasakiensis JCM 18891 T in the phylogenomic tree (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 16S rRNA gene sequence comparison of these highly active chitinolytics with the type strains in the EzBioCloud database showed that eight strains, Sgf 25, Sgm 25/1, Sh 1, Sh 2, Sh 3, Sh 4, Sh 5, and 14G-22, belong to the genus Microbulbifer (family Microbulbiferaceae of the phylum Proteobacteria ); three strains, Sgm 5, Sgm 22, and 14G-20, are representatives of the genus Vibrio (family Vibrionaceae of the phylum Proteobacteria ); the strain V1SW 51 is related to the genus Aquimarina (family Flavobacteriaceae of the phylum Bacteroidetes ); and the strain B530 belongs to the genus Pseudoalteromonas (family Pseudoalteromonadaceae of the phylum Proteobacteria ) [ 42 ]. However, the Vibrio and Pseudoalteromonas isolates have the plural polymorphic 16S rRNA genes that make their species identification difficult without thorough genome-based or species-specific analysis [ 43 , 44 ].…”
Section: Results and Discissionmentioning
confidence: 99%
“…The biosynthetic gene clusters (BGCs) displaying 75% similarity encompass various functionalities, including the synthesis of compounds responsible for membrane fluidity maintenance, branched-chain fatty acids, and the osmolyte ectoine (1,4,5,6-tetrahydro-2-methyl-4-pyrimidine carboxylic acid), which is vital for halophilic microorganism adaptation [ 39 , 40 ]. Notably, ectoine serves as a structural component facilitating survival under unfavorable conditions, with its presence confirmed in the genome of R. erythropolis MGMM8.…”
Section: Discussionmentioning
confidence: 99%